Factors and Principles of Improving the Hierarchical System of Sale of Insurance Products - Abdukhalilovna, Mavrulova Nilufar (Research Parks Publishers, 2023)
The article discusses the issues of managing the sales system in an insurance company, and also analyzes the importance of a vertically integrated sales system for insurance products and its impact on efficiency. Also, when implementing the tariff policy, it is proposed to develop a tariff system for groups of risk factors, and the influence of an insurance company on financial stability is also expressed.